Aplikasi Mobile Tes Kepribadian dengan Metode DISC dan Forward Chaining - Muhammad Rizki Zidan; Agung Triayudi; Ira Diana Sholihati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Information technology plays a big role in various aspects. With technology, which can make it easier for humans to make decisions quickly and effectively. An expert system is an information system that contains knowledge from an expert in order to help with decision making. This system was designed with the theory of Dr. William Moulton Marston to find out his personality and work references. To find out a person, a personality test is carried out. The Personality Test uses a manual version through distributing questionnaires to find out people's dispositions. The evaluation is made a manual version through an answer sheet. Each person takes a lot of duration, this system is made using forward chaining. forward chaining begins the way inference begins with facts to verify the principle of an assumption. The way data is retrieved begins with assumptions until it is completed. The goal is to determine a person's disposition and propose a field of work for their personality. The app also uses Agile development, because the process of upgrading software requires a duration that tends to be fast and does not consume large resources, so modifications according to customer needs can be processed more agilely, and can use input to the development team to prepare methods. The existence of this application can help psychologists and users in the personality test process so that users do not have to come to see a psychologist and more efficiently carry out the personality test process carried out.